Konsep Uzlah dalam Al-Qur’an dan Kontekstualisasinya dalam Pertemanan Generasi Milenial - Yasir, Muhammad; Fikria, Miftahul; Putra, Afriadi (Islamic Religious Education Departement, 2025)
This article discusses the concept of uzlah in the Qur'an and how it is applied in the context of friendship among the millennial generation. This research focuses on the millennial generation’s social challenges, often trapped in shallow relationships. This research explores how the uzlah concept can be applied to modern friendship. The methodology used is library research with a descriptive-analytical approach. The results of the study show that the analysis of Surah Al-Kahf verse 16 and Surah Maryam verses 48-49, concerning the interpretation of Al-Misbah and Tafsir Al-Azhar, reveals three concepts of uzlah that are relevant to the friendship of the millennial generation: first, friendship must be built on the foundation of faith, not just comfort; second, wealth and status cannot be used as a benchmark in choosing friends; third, in establishing friendship, it is essential to place fear and dependence on Allah SWT. This research recommends encouraging millennials to appreciate spiritual values more in building friendships, protecting the heart from spiritual veils, and creating meaningful relationships. Let us dig deeper into these values and make meaningful friendships.